Bicarbonate buffered peritoneal dialysis fluid upregulates angiopoietin-1 and promotes vessel maturation - Eich, Gwendolyn; Bartosova, Maria; Wlodkowski, Tanja; Schäfer, Betti; Pichl, Sebastian; Hackert, Thilo; Schmitt, Claus P. (PLOS ONE, 2017)
Background Ultrafiltration decline is a progressive issue for patients on chronic peritoneal dialysis (PD) and can be caused by peritoneal angiogenesis induced by PD fluids. A recent pediatric trial suggests better preservation of ultrafiltration with bicarbonate versus lactate buffered fluid; underlying molecular mechanisms are unknown. Methods Angiogenic cytokine profile, tube formation capacity and Receptor Tyrosine Kinase translocation were assessed in primary human umbilical vein endothelial cells following incubation with bicarbonate (BPDF) and lactate buffered (LPDF), pH neutral PD fluid with low glucose degradation product content and lactate buffered, acidic PD fluid with high glucose degradation product content (CPDF). Peritoneal biopsies from age-, PD-vintage- and dialytic glucose exposure matched, peritonitis-free children on chronic PD underwent automated histomorphometry and immunohistochemistry. Results In endothelial cells angiopoietin-1 mRNA and protein abundance increased 200% upon incubation with BPDF, but decreased by 70% with LPDF as compared to medium control; angiopoietin-2 remained unchanged. Angiopoietin-1/Angiopoietin-2 protein ratio was 15 and 3-fold increased with BPDF compared to LPDF and medium. Time-lapse microscopy with automated network analysis demonstrated less endothelial cell tube formation with BPDF compared to LPDF and CPDF incubation. Receptor Tyrosine Kinase translocated to the cell membrane in BPDF but not in LPDF or CPDF incubated endothelial cells. In children dialyzed with BPDF peritoneal vessels were larger and angiopoietin-1 abundance in CD31 positive endothelium higher compared to children treated with LPDF. Conclusion Bicarbonate buffered PD fluid promotes vessel maturation via upregulation of angiopoietin-1 in vitro and in children on dialysis. Our findings suggest a molecular mechanism for the observed superior preservation of ultrafiltration capacity with bicarbonate buffered PD fluid with low glucose degradation product content.